Left ventricular pseudoaneurysm: a challenging diagnosis. - Faustino, M (2016)
Left ventricular pseudoaneurysm is a rare complication of acute myocardial infarction, associated with high mortality. However, it can present in a non-specific manner, complicating and delaying the diagnosis. The authors present the case of a 65-year-old patient, hypertensive, with no other known relevant medical history, who presented with chest pain, cough and left pleural effusion, initially attributed to a pulmonary process. However, these were in fact the result of a left ventricular pseudoaneurysm following silent acute myocardial infarction. The diagnosis was suspected on echocardiography and confirmed by cardiac magnetic resonance imaging, and the patient underwent successful surgical pseudoaneurysm repair. This case illustrates an atypical presentation of a left ventricular pseudoaneurysm, in which the manifestations resulted from pericardial and pleural extension of the inflammatory process associated with contained myocardial rupture. The case demonstrates the need for a high index of suspicion, and the value of imaging techniques to confirm it, in order to proceed with appropriate surgical treatment, and thus modify the course of the disease.